1/2d-3;d=0

Simple and best practice solution for 1/2d-3;d=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/2d-3;d=0 equation:



1/2d-3d=0
Domain of the equation: 2d!=0
d!=0/2
d!=0
d∈R
We add all the numbers together, and all the variables
-3d+1/2d=0
We multiply all the terms by the denominator
-3d*2d+1=0
Wy multiply elements
-6d^2+1=0
a = -6; b = 0; c = +1;
Δ = b2-4ac
Δ = 02-4·(-6)·1
Δ = 24
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$d_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$d_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{24}=\sqrt{4*6}=\sqrt{4}*\sqrt{6}=2\sqrt{6}$
$d_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{6}}{2*-6}=\frac{0-2\sqrt{6}}{-12} =-\frac{2\sqrt{6}}{-12} =-\frac{\sqrt{6}}{-6} $
$d_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{6}}{2*-6}=\frac{0+2\sqrt{6}}{-12} =\frac{2\sqrt{6}}{-12} =\frac{\sqrt{6}}{-6} $

See similar equations:

| x=√63 | | p+1.6-4;p=5 | | 15-9=5x-3x | | n+4/3=9/10 | | 7x/5=28 | | 4x-7x+48=2x+38 | | 6w-2;w=1 | | -3n+2=-4n-4 | | x-5.5=-6.5 | | x^2+14x-3=3 | | 7x+2=2x+16 | | 2^9x=1/8 | | -5=2+h | | 4/9=z+4/7 | | 1.4=n+12 | | 0.60x+48=-0.80x+97 | | p+3/5-p-4/2=2 | | -11=c/7 | | d+4=-5 | | 4.8=x-5.1 | | 4(2x-10=16 | | −1,316+188m=0 | | 35=7/11x | | v-6=42 | | 4(3x+10)=5+9x | | 4(x-1/2)=6/7 | | 7a-6=-1-11a | | 6(x-2)=4x+2x+ | | 3(x+9)^2+12=0 | | -15a-18=6a+16 | | -1.5q^2-5q=0 | | 4m^2+8m=21 |

Equations solver categories